A dual-scale modelling approach for creep-fatigue crack initiation life prediction of holed structure in a nickel-based superalloy. (January 2022) - Li, Kai-Shang; Cheng, Lv-Yi; Xu, Yilun; Wang, Run-Zi; Zhang, Yong; Zhang, Xian-Cheng; Tu, Shan-Tung; Miura, Hideo
Highlights: Macro-to-micro FEM with dual-scale modelling approach for holed structures. Accurate crack initiation life prediction abilities within ±2.0 error band. Simulated crack initiation sites in consistency with microstructure observations. Potential values for the dual-scale approach in scientific and engineering aspects. Abstract: In this paper, a dual-scale modelling approach is developed to investigate creep-fatigue behavior and predict crack initiation life for holed structures under multi-axial stress state. The macro-scale simulation supplies local deformation histories to the dual-scale simulation as boundary conditions. In the dual-scale simulation process, the micro-mechanical behavior and damage evolution are described by using crystal plasticity. In order to validate the dual-scale simulation procedures, a series of creep-fatigue tests as well as the post-test characterizations were carried out for nickel-based Inconel 718 at 650 ℃. The detailed results of macro- and micro-scale simulations are presented in terms of stress–strain behavior, damage evolution and life prediction. Regarding the macro-scale simulations as the benchmark, it may provide an assistant support and precognition for the micro-scale damage calculation at higher cycles. The predicted cycle numbers to crack initiation are in agreement with the experimental ones. More advantages are manifested in the potential scientific and engineering significance for the dual-scale modelling approach.